Exploration of Bioactive Compounds from Agricultural Waste for the Development of Value-Added Products - Judijanto, Loso; Widodo, Imam; Mariay, Ivonne Fitri; Tuhumena, Veronica L.; Sarungallo, Amelia S. (West Science Agro, 2025)
Agricultural waste is a rich yet underutilized resource for bioactive compounds that have significant potential in pharmaceuticals, cosmetics, and functional food industries. This study systematically analyzed 23 peer-reviewed articles from the Scopus database to identify the types of bioactive compounds present in agricultural waste, the extraction methods used, their applications, and associated challenges. The findings revealed that phenolics, flavonoids, tannins, carotenoids, and saponins are the most commonly identified bioactive compounds. Advanced extraction techniques such as ultrasound-assisted and supercritical fluid extraction demonstrated superior efficiency compared to conventional methods. Applications of these compounds span health, wellness, and food sectors, supporting sustainable development and the circular economy. However, challenges including high extraction costs, standardization issues, and regulatory hurdles must be addressed to realize their full potential. This study emphasizes the need for further research and collaboration to enhance the valorization of agricultural waste and unlock its economic and environmental benefits.